2016
DOI: 10.1111/jbg.12225
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fitting dominance and additive effects on accuracy of genomic prediction of breeding values in layers

Abstract: Most genomic prediction studies fit only additive effects in models to estimate genomic breeding values (GEBV). However, if dominance genetic effects are an important source of variation for complex traits, accounting for them may improve the accuracy of GEBV. We investigated the effect of fitting dominance and additive effects on the accuracy of GEBV for eight egg production and quality traits in a purebred line of brown layers using pedigree or genomic information (42K single-nucleotide polymorphism (SNP) pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 37 publications
3
19
0
Order By: Relevance
“…Genomic selection models with dominance have been tested in several populations, including dairy cattle (Ertl et al, 2014 ; Aliloo et al, 2016 ; Jiang et al, 2017 ), pigs (Esfandyari et al, 2016 ; Xiang et al, 2016 ), sheep (Moghaddar and van der Werf, 2017 ), and layers (Heidaritabar et al, 2016 ) with ambiguous results. Jiang et al ( 2017 ) found a negligible percentage of variation explained by dominance effects for productive life in a Holstein cattle population, although Ertl et al ( 2014 ) suggested that dominance may suppose up to 39% of the total genetic variation for Somatic Cell Score in a population of Fleckvieh cattle.…”
Section: Genomic Selection Models With Dominancementioning
confidence: 99%
“…Genomic selection models with dominance have been tested in several populations, including dairy cattle (Ertl et al, 2014 ; Aliloo et al, 2016 ; Jiang et al, 2017 ), pigs (Esfandyari et al, 2016 ; Xiang et al, 2016 ), sheep (Moghaddar and van der Werf, 2017 ), and layers (Heidaritabar et al, 2016 ) with ambiguous results. Jiang et al ( 2017 ) found a negligible percentage of variation explained by dominance effects for productive life in a Holstein cattle population, although Ertl et al ( 2014 ) suggested that dominance may suppose up to 39% of the total genetic variation for Somatic Cell Score in a population of Fleckvieh cattle.…”
Section: Genomic Selection Models With Dominancementioning
confidence: 99%
“…The Gibbs sampler also allows to calculate posterior distributions of the any combination of parameters of the model. Thus, we calculated for each iteration of the Gibbs sampler the following approximations for the additive and dominance genetic variances [ 47 ] as: where is the number of individuals in the population and and the breeding and the dominance deviation values for the - th individual. They were calculated as: where as defined by Xiang et al [ 13 ], was the observed allelic frequency for the - th SNP and Note that this parameterization implies a population under Hardy–Weinberg equilibrium and that the covariance between the breeding values and dominance deviations is equal to zero.…”
Section: Appendixmentioning
confidence: 99%
“…However, Ertl et al (2014) reported a range of low to very high ratio of dominance to total genetic variance for 9 milk production and conformation traits in Fleckvieh cattle and between 3.3% and 50.5% of the total genetic variance. Heidaritabar et al (2016) reported the ratio of dominance to phenotypic variance in egg production traits in purebred layer hens from 3.0% to 22% based on pedigree BLUP, from 0.0% to 3.0% based on GBLUP and from 1.0% to 5.0% based on a Bayesian approach (BayesC).…”
Section: Introductionmentioning
confidence: 99%